Time Limitation of Punishability and Activity of Police Teams dealing with undetected crime – the Police X Archives - Stańczyk, Krystian M. (Acta Universitatis Lodziensis. Folia Iuridica, 2018)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-fareast-language: EN-US; mso-bidi-font-style: italic; mso-ansi-language: PL; mso-bidi-language: AR-SA;">The Police Teams dealing with undetected crime, commonly known the Police X Archives have long been a part of the structure of Polish law enforcement agencies being an important element of the State’s instruments in the fight against crime. These groups were entrusted with a particular type of cases which cover cases of the most severe crimes (primarily murders) and unexplained events, committed many years ago, ended with negative results due to an undetected perpetrator or lack of sufficient evidence of their guilt. This article attempts to illustrate the specificities of the Police X Archives. It has also been pointed out how strong the presence of the institution of the time limitation of punishability is in work of such a team. Considering the effects of the time limits associated with it, it not only has led to the decision to create the Police X Archives, but it also influences their actions in many areas.